2019
DOI: 10.1002/pc.25250
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐phase separation kinetics of polyurethane nanocomposites with neural network

Abstract: Thermoplastic polyurethane elastomers (TPUs) reinforced with multi wall carbon nanotubes (MWCNTs) and Closite30B, were prepared via melt mixing approach and investigated by spectroscopy, and rheological analyses. Following basic analyses, time sweep tests were used to determine the influence of temperature, applied preshear and nanofiller content and aspect ratio on the micro‐phase separation kinetics of the nanocomposites. Based on the experimental results, artificial neural network was developed to explain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…This dependences was confirmed by Niemczyk et al [31]. Jouibari et al [32] synthesized poly(etherurethane)s, which showed 0.7 of DPS value. Fuensanta et al [33] synthesized thermoplastic polyurethane coatings with mixture of polyethers.…”
Section: Ftirmentioning
confidence: 56%
“…This dependences was confirmed by Niemczyk et al [31]. Jouibari et al [32] synthesized poly(etherurethane)s, which showed 0.7 of DPS value. Fuensanta et al [33] synthesized thermoplastic polyurethane coatings with mixture of polyethers.…”
Section: Ftirmentioning
confidence: 56%
“…1 Polymer networks (physical or chemical) with elastic nature possess high shape memory performance. 2 Polyurethanes (PUs) are great candidates for shape memory biomaterials with semi-crystalline or amorphous soft domains, acting as the switching component, and hard domains with higher rigidity, acting as the permanent component. 3 Polyurethanes are segmented copolymers comprised of soft and hard segments.…”
Section: Introductionmentioning
confidence: 99%
“…1). To this end, bands of free and hydrogen-bonded N H stretching vibrations at respective wavenumbers of 3445 and 3348 cm −1 were followed and the degree of microphase separation (DPS) was calculated using Eqn (1) 30 :…”
Section: Resultsmentioning
confidence: 99%
“…During the microphase separation process, the large surface of MWCNTs can act as a platform to assist hard domain formation, and thus adsorption of stiffer blocks on the surface of MWCNTs would be favored. 33 The Avrami equation was also used to study the microphase separation behavior of the samples using the results of time sweep rheological measurements (Eqn (3)) 34,35 :…”
Section: Rheological Measurementsmentioning
confidence: 99%